Acquisition as entry modes: winning or losing? - Mohd Salleh, Rezashah; Seth, Mohd Hareth; Shaharuddin, Nur Diyana; Syed Ahmad Razali, Syed Hasif Emir; T.K. Muthu Koya Thangal, Thahira Bibi; Mohd Yassin, Yasni Nurul Huda (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study assesses either acquisition of KD Hotel is the wise decision made by Malazure Eko Group due to the difference aspects crossroads of Europe and Asia culture as well as values. The analysis is based on a qualitative and quantitative approach where an interview was conducted with the hotel general manager and questionnaires were distributed for further clarification. It’s been found that the acquisition made by Malazure Eko Group to purchase the hotel is successful as it is in a strong position and needs to focused on marketing development to sustain its position among the other competitors